Implementation of Aerosol-Cloud Interaction within WRF-CHIMERE Online Coupled Model: Evaluation and Investigation of the Indirect Radiative Effect from Anthropogenic Emission Reduction on the Benelux Union - Tuccella, Paolo; Menut, Laurent; Briant, Régis; Deroubaix, Adrien; Khvorostyanov, Dmitry; Mailler, Sylvain; Siour, Guillaume; Turquety, Solène (Atmosphere, 2019)
The indirect effects of aerosol are particularly important over regions where meteorological conditions and aerosol content are favourable to cloud formation. This was observed during the Intensive Cloud Aerosol Measurement Campaign (IMPACT) (European Integrated project on Aerosol Cloud Climate and Air quality Interaction (EUCAARI) project) in the Benelux Union during May 2008. To better understand this cloud formation variability, the indirect effects of aerosol have been included within the WRF-CHIMERE online model. By comparing model results to the aircraft measurements of IMPACT, to surface measurements from EMEP and AIRBASE and to MODIS satellite measurements, we showed that the model is able to simulate the variability and order of magnitude of the observed number of condensation nuclei (CN), even if some differences are identified for specific aerosol size and location. To quantify the impact of the local anthropogenic emissions on cloud formation, a sensitivity study is performed by halving the surface emissions fluxes. It is shown that the indirect radiative effect (IRE) at the surface is positive for both shortwave and longwave with a net warming of +0.99 W/m2. In addition, important instantaneous changes are modelled at local scale with up to ±6 °C for temperatures and ±50 mm/day for precipitation.